Music theory and its sources: Antiquity and the middle ages - Barbera, André (Indiana University of notre dame press, 1990)
This collection of essays argues that early music theory is more interesting than commonly held and that its broad and loose definition in antiquity and the Middle Ages allows for the inclusion of a plethora of intellectual pursuits under the heading of "Music Theory".